Millenial Netiquette In Doing Muamalah And Warding Off Hoaxes On Social Media Based On MUI Fatwa Number 24 Of 2017 - Puput Yanita Senja; Ade Yuliar; Fathurrohman Husen (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2022)
MUI Fatwa Number 24 of 2017 contains The Laws and Guidelines for Doing Muamalah Through Social Media. The MUI Fatwa can be applied to social networking ethics (netiquette). The millennial generation has excellent power in countering hoax narratives. The research purpose was to determine netiquette of the millennial generation in doing muamalah and warding off hoax in social media based on MUI Fatwa. The design of this study is qualitative research using an online qualitative survey. Netiquette as a guideline based on the MUI Fatwa focuses on discussing guidelines for doing muamalah on social media and creating and disseminating related content/information in countering hoaxes by the millennial generation from the four existing guidelines. Millennial's netiquette in doing muamalah on social media should be done properly and correctly, not violating the Shari'a and regulations (MUI Fatwa and others), and responding well to each other's content. The content shared is positive and not a hoax. Millennials sort out contents that will be disseminated on social media by studying, understanding, confirming, then following. The netiquette for millennials in warding off hoaxes is to ensure that the content is appropriately verified, helpful, not provocative and does not contain hoaxes, slander, backbiting, bullying, gossip, and other forbidden things. Millennials avoid spreading hoax content on social media by limiting accounts, avoiding and discontinuing, seeking truth from trusted sources, following the Indonesia Anti Hoax page, reporting harmful content through content complaints websites, or directly using the block and report features on social media. If this is not possible, they choose to remain silent, skip, and not share that hoax content.